THE NEEDS AND PROBLEMS OF ENGLISH SKILL FOR THE HOTEL FRONT OFFICE STAFF AT LOMBOK WEST NUSA TENGGARA - Siti Lathifah (Media Bina Ilmiah, 2022)
This study aims to determine the description of the application of empowerment, motivation and employee performance, as well as to analyze and explain the influence between variables jointly or partially. Data was collected through questionnaires, interviews and documentation techniques. Research place at PT Industri Telekomunikasi Indonesia. The sample used was 67 employees from various divisions. The sampling technique used random sampling method. The verification analysis of the data used is multiple linear regression analysis. The results of the research show that data analysis: (1) employee empowerment has a significant positive effect on employee performance, (2) motivation has a positive but not significant effect on performance. (3) employee empowerment, knowledge management and motivation simultaneously have a significant positive effect on employee performance. The results showed that employee empowerment and motivation together had a positive and significant effect on performance, but partially the effect of motivation on performance had a positive but not significant effect. This means that the influence of motivation on performance does not apply in general, and only applies in this study